Sistem Billboard Digital Cerdas Menggunakan Metode Jaringan Syaraf Tiruan dengan Orientasi Pendeteksi Jarak dan Usia - Wicaksono, Teguh Adiaksa; Nachrowie, Nachrowie; Mujahidin, Irfan (Program Studi Teknik Elektro Universitas Khairun, 2021)
The development of technology in an increasingly sophisticated industrial era is evidenced by the presence of modern equipmentproduced to speed up and simplify a job. In Advertising currently has no filtering about the age of its readers. Based on this background this study built a system for billboard display (advertising) based on age. For the method used using the method of artificial neural networks. For testing the tool uses distance parameters based on objects that are indexed with two categoriesÃ‚Â namely adults and children. For the test results using 4 objects of people with a distance of 1 meter to 5 meters per object obtained the resultsdetected each adult and small children distanced 1 meter to 3 meters in a distance of 4 meters to 5 meters undetected with an accuracy of 80%.